NEW METHOD OF EPIDEMIOLOGICAL EVALUATION OF THE INCIDENCE OF COMPLICATIONS AFTER ANTI-TUBERCULOSIS VACCINATION - S. N. Shugaeva; E. D. Savilov (Туберкулез и болезни лёгких)
The article offers a new method for calculation of incidence of complications after primary anti-tuberculosis vaccination. Using the example of analysis of continuous sampling of complications after anti-tuberculosis vaccination (n = 110) in Irkutsk Region in 2005-2014 the article shows the advantage of the offered method compared to the existing ones.